Willed action and attention to the selection of action. - Lau, H; Rogers, R; Ramnani, N; Passingham, R (2004)
Actions are said to be 'willed' if we consciously pay attention to their selection. It has been suggested that they are associated with activations in the dorsal prefrontal cortex (area 46). However, because previous experiments typically used a 'free selection' paradigm to examine this hypothesis, it is unclear whether the results reflected the attention to the selection of action or the freedom of choice allowed by the tasks. In this experiment, we minimized the difference of working memory demand across task conditions by using novel stimuli in each trial. We found that activation in the dorsal prefrontal cortex on a free selection task was not significantly different from that induced by another task that required attention to the selection of action, although the responses were externally specified. This suggests that the dorsal prefrontal cortex is in fact associated with attention to the selection of action, but does not play a unique role in the generation of internally initiated actions. However, the presupplementary motor area (pre-SMA) may subserve this function as activity in this region was found to be tightly associated with the free selection of responses.